Socialization and Extension of Green Economy to PKK Group and Farmer Groups - Patonah, Siti; Ma'mun, Hisyam; Subekti, Ervina Eka; Supriyanto, Eka Adi (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2025)
Protecting the environment and ensuring its sustainability for future generations are sustainable development goals (SDGs). A preserved environment and ensuring sustainability for future generations is a sustainable development goal (SDGs). Every human activity produces waste that, if not appropriately managed, can bring problems in the future. Before starting a production process that utilizes natural resources, a complete understanding of the "green economy" is required.  This activity aims to provide socialization and counseling for partners in the assisted village empowerment program (GDP) about the "green economy" as the first step in building a pineapple center assisted village in Mendelem village, Belik District, Pemalang Regency. The method used is participatory action research. Five steps are taken to use the method: socialization, training, technology application, mentoring, and evaluation. The results were: an increase in partners' understanding of green economy reached 17%; partners' understanding of green economy practices reached 70.37%.  The practice of a green economy has a higher score than understanding. Partners feel helped by the direct practice of the green economy concept in the production process of processed pineapples.